Critical Material Culture Analysis in US National Register of Historic Places Significance Statements. (17th February 2022) - Morgan, Rachel
ABSTRACT: Significance statements express the values of archaeological assemblages and effect the preservation of sites in the United States. Through an evaluation of 219 significance statements from the South Carolina Sandhills, this paper explores trends in the analysis of material culture in Section 106 and Section 110 assessments. A review of archaeological guidelines from 47 states contextualizes the patterns of material culture analysis observed in the Sandhills. This research indicates an overreliance on subjective quantification measures and undefined artifact density calculations fostered by the absence of robust material culture analysis recommendations in state guidelines. A consideration of the impact bias in National Register of Historic Places recommendations suggests that modifications to state guidelines, university curricula, and historic contexts are necessary to address the systems that permit the perfunctory treatment of material culture in compliance archaeology.